Effect of Telephone Counseling on the Nutritional Status and Physical Activity in Iranian Middle-Aged Women - Behnaz Enjezab; Behnaz Rahbarnia; Mahshid Bookaie; Ali Dehghani (Golestan University of Medical Sciences, 2021)
Background: Lifestyle modification is an important factor in promoting the health of middle-aged women. Therefore, this study aimed to determine the effect of telephone counseling on the nutritional status and physical activity of middle-aged women in Yazd, Iran. Methods: This randomized controlled clinical trial was done on 50 middle-aged women during September to February 2017. Eligible women was recruited from religious places and then were randomly assigned into two intervention and control groups. The participants in the intervention group received the counseling program in 8 calls for 20-30 minutes twice per week. The control group received no intervention. Data were gathered using a health promoting life-style questionnaire for middle-aged women in three time points; before intervention, immediately, and one month after the intervention. Data were analyzed in SPSS 16 software using Chi-square, repeated measures ANOVA and independent t-test. A significance level was considered P<0.05. Results: There was no significant difference between the two groups in terms of nutritional status and physical activity (PA) before the intervention, but there was significant difference between them immediately and one month after the intervention. Also adjusting the baseline values, repeated measures ANOVA test showed a significantly premiere mean of nutritional status in telephone counseling compared to the control group (P<0.001). Conclusion: The results of the study showed that telephone counseling significantly improved the lifestyle of the middle-aged women. Also, recommended that health care providers use of telephone counseling that effective and efficient tool for promoting womenchr('39')s health.